Comunicação, privacidade e identificação: Google e a formação do julgamento veloz de marcas na visibilidade mediática - Forni, Decio Ferreira (2013)
This research project focuses on the evaluation of brands by Web users. To this end, an investigation is made of processes that lead to the formation of judgments about brands and their products/services via the Internet, based on the rapid identification and interactive assessment of texts, videos and images, among other data of an opinionative nature. Today, these mechanisms of judgment, triggered impulsively and taking place through searches, occur on the plane of mediatic visibility and may lead to moral and financial losses in the localization of people and brand-related data. As a strategy of defense against criticisms, companies, in turn, use technological, legal and content-related tactics that need to be understood fully and accurately. The importance of this study stems from a rare context of identification, be it from a social standpoint, in which instances of judgment occur continuously, or from the moral standpoint in terms of how we still deal with the right to freedom of expression. Laws pertaining to these rapid mechanisms are currently under discussion in Brazil, but with little applied research that demonstrates the advantages and risks implied in the process. The theoretical argument of this thesis is based on the history of the theoretical perspectives of mediatic visibility in the 20th century, focusing on the Frankfurt School (in the works of Benjamin and the observation of society at a local level, through the flâneur) and the Toronto School (in McLuhan, concerned with the means that lead to a global outlook). In addition, the theoretical perspectives of two themes are described that were transformed with the advent of mass media and the digital era, i.e., privacy and identification, the former discussed by Ariès and Lacan, and the latter by Foucault, Barthes and Lyon. The viability of privacy will be questioned from a cybercultural viewpoint, with information accessible at an unmatched speed, which are themes addressed based on Castells, Levy, Virilio and Trivinho, as well as authors who discuss prosumers, such as Kerckhove, Benkler and Tapscot. An empirical investigation into rapid brand judgment will be conducted via Google, starting from a literature review that encompasses Semprini s concepts about brands, Greimas s elements of semiotics, and semantic assessment from the viewpoint of communication ecology. The empirical delimitation of the study involved eighteen categories of products ranked by the Brazilian print media and their corresponding judgments on the first pages of Google. The main findings reveal significant differences in comparisons of conventional and rapid judgments, indicating the importance of decentralized communication, which may be affected by the current control of the Internet